vBarriers and facilitators of adherence to TB treatment in patients on concomitant TB and HIV treatment: a qualitative study - Frich Jan C; Bjune Gunnar A; Gebremariam Mekdes K (BMC, 2010)
Abstract Background Tuberculosis is a major public health problem in Ethiopia, and a high number of TB patients are co-infected with HIV. There is a need for more knowledge about factors influencing treatment adherence in co-infected patients on concomitant treatment. The aim of the present study is to explore patients' and health care professionals' views about barriers and facilitators to TB treatment adherence in TB/HIV co-infected patients on concomitant treatment for TB and HIV. Methods Qualitative study using in-depth interviews with 15 TB/HIV co-infected patients and 9 health professionals and focus group discussions with 14 co-infected patients. Results We found that interplay of factors is involved in the decision making about medication intake. Factors that influenced adherence to TB treatment positively were beliefs in the curability of TB, beliefs in the severity of TB in the presence of HIV infection and support from families and health professionals. Barriers to treatment adherence were experiencing side effects, pill burden, economic constraints, lack of food, stigma with lack of disclosure, and lack of adequate communication with health professionals. Conclusion Health professionals and policy makers should be aware of factors influencing TB treatment in TB/HIV co-infected patients on concomitant treatment for TB and HIV. Our results suggest that provision of food and minimal financial support might facilitate adherence. Counseling might also facilitate adherence, in particular for those who start ART in the early phases of TB treatment, and beliefs related to side-effects and pill burden should be addressed. Information to the public may reduce TB and HIV related stigma.